PENGARUH PAJAK LANGSUNG DAN PAJAK TAK LANGSUNG TERHADAP KESEJAHTERAAN KONSUMEN (STUDI KASUS PAJAK KENDARAAN BERMOTOR RODA DUA DI KOTA PONTIANAK) - B01112025, YELSI SURYA (Jurnal Pembangunan dan Pemerataan, 2017)
This study aims to analyze the effect of direct tax and indirect tax on consumer welfare on a two-wheeled motor vehilcle tax in the city of Pontianak. This study was a descriptive study. The data that has been processed and analyzed using descriptive statistical analysis tools. The results showed that the effect of direct taxes (vehicle tax) higher than the level of satisfaction with indirect taxes (sales tax). This shows that consumers would rather pay taxes direct taxes Indirect Taxes than . On the consumption curve, the consumer will get the level of prosperity as the number of high income without any tax imposed producers to consumers and consumers will receive their welfare level is the lowest is at point B, namely income Y1 E1 consumption.   Keywords: Direct Tax, Indirect Tax and Consumer welfare